How mindfulness-based cognitive behavior therapy and assertiveness training can reduce postpartum depression - Fitri Dia Muspitha; Heni Dwi Windarwati; Fransiska Imavike Fevriasanty (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Postpartum depression is a maternal mental health problem that must be treated immediately because it will have a negative impact on the mental health of mothers and babies. Mindfulness-based cognitive behavior therapy (MCBT) and Assertiveness Training are effective short-term psychological interventions that can overcome psychological symptoms such as postpartum depression. The purpose of this study was to determine the effect of Mindfullness based on Cognitive Behavior Therapy and Assertiveness Tarining on reducing symptoms of postpartum depression. The research design used a quasi-experimental method with a pretest-posttest non-equivalent control group design. The study sample amounted to 76 which were divided into two groups, namely the intervention group (38 people) and the control group (38 people). The study was conducted at the Dau Health Center, East Java in September-November 2022 using a research instrument in the form of an Edinburg postpartum depression scale (EPDS) questionnaire. The statistical tests used are the Wilcoxon and Mann-Whitney tests. The results showed that there was a statistically significant difference, namely a decrease in depressive symptoms given by MCBT and AT therapy compared to the provision of deep breath relaxation techniques therapy with value of p = 0.000. Psychological therapy that combines MCBT and AT is more effective against reducing symptoms of postpartum depression. Abstrak: Depresi postpartum merupakan masalah kesehatan jiwa maternal yang harus segera ditangani karena akan berdampak negatif pada kesehatan mental ibu dan bayinya. Intervensi terapi psikoterapi Mindfullness berbasis cognitive behavior therapy (MCBT) dan Assertiveness Training merupakan intervensi psikologis jangka pendek yang efektif dapat mengatasi gejala psikologis seperti depresi postpartum. Tujuan penelitian ini untuk mengetahui pengaruh Mindfullness berbasis Cognitive Behavior Therapy dan Assertiveness Tarining terhadap penurunan gejala depresi postpartum. Desain penelitian menggunakan metode Quasi-experimental dengan rancangan pretest-posttest non equivalent control group design. Sampel penelitian berjumlah 76 yang dibagi menjadi dua kelompok yaitu kelompok intervensi (38 orang) dan kelompok kontrol (38 orang). Penelitian dilakukan di Puskesmas Dau Jawa Timur pada bulan September-November tahun 2022 dengan menggunakan istrumen penelitian berupa kuesioner Edinburg postpartum depression scale (EPDS). Uji statistik yang digunakan yaitu uji Wilcoxon dan Mann-Whitney. Hasil penelitian menunjukan bahwa terdapat perbedaan yang signifikan secara statistik yaitu terjadi penurunan gejala depresi yang diberikan terapi MCBT dan AT dibandingkan dengan pemberian terapi tehnik relaksasi nafas dalam dengan nilai p = 0.000 . Terapi psikologis yang dikombinasikan MCBT dan AT lebih efektif terhadap penurunan gejala depresi postpartum.